PatOMat - Versatile Framework for Pattern-Based Ontology Transformation - Zamazal, Ondřej; Svátek, Vojtěch (Computing and Informatics, 2015)
The purpose of the PatOMat transformation framework is to bridge between different modeling styles of web ontologies. We provide a formal model of pattern-based ontology transformation, explain its implementation in PatOMat, and manifest the flexibility of the framework on diverse use cases.